ANALISIS PERMINTAAN KENTANG DI KOTA DENPASAR SERTA FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Ida Bagus Putu Surya Dharmendra; I Made Budiasa; Luh Putu Kirana Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
Potatoes (Solanum tuberosum L.) is one of the important horticultural commodities because it is an alternative food ingredient supporting food diversification programs. The demand for potatoes is increasing along with the development of the snack industry and fast food restaurants that use potato ingredients. This study is titled Analysis of Potato Demand in Denpasar City and Factors That Affect It. The purpose of this study is to analyze the function of demand and elasticity of potato demand in Denpasar City and to analyze factors that affect potato demand in Denpasar City. Determination of research locations in Badung Market, Kreneng Market and Sanglah Market is done deliberately (purposive sampling) based on several reasons. Determination of the number of samples for potato consumers is determined by proportional random sampling method using the formula Slovin. Based on the population of 93 traders, samples were obtained in Kreneng Market as many as 14 respondents, 25 respondents in Sanglah Market and 54 respondents in Badung Market. The data analysis method used in this study is a qualitative descriptive method using multiple linear regression analysis. Based on the results of the study, it was concluded: 1) The function and elasticity of potato demand in Denpasar City, namely, Qd = 3,38.X1 -1,257.X2 -1,948.X3 0,056.X4 0.249 and the elasticity of potato prices to potato demand is elastic, 2) Factors that affect potato demand in Denpasar City are potato prices and carrot prices